173k views
2 votes
Simplify:
(1)/(√(5)-√(7)+√(12))

User Jecfish
by
5.2k points

2 Answers

5 votes

Answer:

Multiply the numerator and denominator by the conjugate.

Exact Form:

1√5−√7+2√3

Decimal Form:

0.75267290…

User Roninblade
by
5.4k points
1 vote

Make use of the difference of squares identity,


a^2-b^2=(a-b)(a+b)

Let
a=\sqrt5-\sqrt7 and
b=√(12). Then


\frac1{(\sqrt5-\sqrt7)+√(12)}\cdot((\sqrt5-\sqrt7)-√(12))/((\sqrt5-\sqrt7)-√(12))=((\sqrt5-\sqrt7)-√(12))/((\sqrt5-\sqrt7)^2-(√(12))^2)=(\sqrt5-\sqrt7-√(12))/(5-2√(35)+7-12)=-(\sqrt5-\sqrt7-√(12))/(2√(35))

Now multiply the numerator and denominator by √(35):


-(\sqrt5-\sqrt7-√(12))/(2√(35))\cdot(√(35))/(√(35))=-((\sqrt5-\sqrt7-√(12))√(35))/(70)=-(5\sqrt7-7\sqrt5-2√(105))/(70)

User CamiloEr
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.